Staphylococcal species heterogeneity in the nasal microbiome following antibiotic prophylaxis revealed by tuf gene deep sequencing. Issue 1 (December 2016) - McMurray, Claire; Hardy, Katherine; Calus, Szymon; Loman, Nicholas; Hawkey, Peter
Abstract Background Staphylococci are a major constituent of the nasal microbiome and a frequent cause of hospital-acquired infection. Antibiotic surgical prophylaxis is administered prior to surgery to reduce a patient's risk of postoperative infection. The impact of surgical prophylaxis on the nasal staphylococcal microbiome is largely unknown. Here, we report the species present in the nasal staphylococcal microbiome and the impact of surgical prophylaxis revealed by a novel culture independent technique. Daily nasal samples from 18 hospitalised patients, six of whom received no antibiotics and 12 of whom received antibiotic surgical prophylaxis (flucloxacillin and gentamicin or teicoplanin +/− gentamicin), were analysed bytuf gene fragment amplicon sequencing. Results On admission to hospital, the species diversity of the nasal staphylococcal microbiome varied from patient to patient ranging from 4 to 10 species. Administration of surgical prophylaxis did not substantially alter the diversity of the staphylococcal species present in the nose; however, surgical prophylaxis did impact on the relative abundance of the staphylococcal species present. The dominant staphylococcal species present in all patients on admission wasStaphylococcus epidermidis, and antibiotic administration resulted in an increase in species relative abundance. Following surgical prophylaxis, a reduction in the abundance ofStaphylococcus aureus was observed in carriers, but not a complete eradication. Conclusions Utilising thetuf gene fragment has enabled a detailed study of the staphylococcal microbiome in the nose and highlights that although there is no change in the heterogeneity of species present, there are changes in abundance. The sensitivity of the methodology has revealed that the abundance ofS. aureus is reduced to a low level by surgical prophylaxis and therefore reduces the potential risk of infection following surgery but also highlights thatS. aureus does persist.